Teaching Chinese in Canada: epics of three Chinese scholars. Issue 1 (4th December 2018) - Lan, Kenneth
Abstract : Purpose: The purpose of this paper is to reveal the development of Chinese studies in selective Canadian universities through examining the remarkable careers of three middle-aged ethnic Chinese intellectuals. Design/methodology/approach: This paper analyses the origin and growth of East Asian Studies programs in Canada by first describing the backgrounds of the three scholars. Why did Canadian universities accept them despite their Chinese origin? Findings: Canadian universities are indeed the incubators of racial tolerance. Racism existed in the 1950s but was only confined to the collegial level. Universities generally welcomed a diversified representation of their payroll. While none of three academics founded East Asian Studies programs in their institutions, they had forcibly become their mascots and had lured more students into lifelong studies of the Far East. Despite the early fanfare of their recruitments, all three had become disillusioned with their employers as years passed. They felt their contributions were taken for granted and had shifted their career focuses elsewhere. The Asia-Pacific is still marginally focussed in the Canadian academe. Originality/value: The three men and many others in the field have sowed the seed for the study of China and the East Asian region in Canada. It is up to future "East Asianists" to carry on this tradition that they had built in the twentieth century.